The influence of global uncertainty on the cross-border performance appraisal: A real options approach. Issue 1 (28th January 2014) - Maley, Jane; Kramer, Robin
Abstract : Purpose: – The aim of this paper is to examine the practice of performance management in a cross-border context in times of global uncertainty. Design/methodology/approach: – This is a conceptual paper. Findings: – The findings expose global uncertainty to be wielding a significant influence on performance management. Practical implications: – A practical framework is developed using real options theory. This approach offers suggestions for multinational corporations to increase the effectiveness of their performance management while at the same time focusing on profit-maximisation. Originality/value: – This paper enhances international management research by recognizing that real options theory can effectively be applied to improve the effectiveness of performance management in global uncertainty.